Synthesis, Comparative Characterization and Photocatalytic Application of SnO2/MWCNT Nanocomposite Materials - Nemeth, Z.; Pallai, Z.; Reti, B.; Balogh, Z.; Berkesi, O.; Baan, K.; Erdohelyi, A.; Horvath, E.; Veréb, G.; Dombi, A.; Forró, L.; Hernadi, K. (Journal of Coating Science and Technology, 2014)
Two different preparation methods were developed to cover successfully multi-walled carbon nanotubes (MWCNT) with tin-dioxide (SnO2) nanoparticles using SnCl2·2H2O as precursor under different solvent conditions. The applied mass ratios of the components were 1:4, 1:8, 1:16, 1:32 and 1:64, respectively. As-prepared tin-dioxide coverages were characterized by TEM, SEM, SEM-EDX, Raman microscopy, BET and X-ray diffraction techniques. Photocatalytic efficiencies of selected composites were investigated in a self-made photoreactor, equipped with UV-A fluorescence lamps. Photocatalytic degradation of phenol solution was followed by using HPLC. Observations revealed that using hydrothermal method we can easily control the layer of SnO2 nanoparticles on the surface of MWCNTs. Using various solvents SnO2 nanoparticles with different morphologies formed. The nanocomposites have low photocatalytic efficiencies under conditions used generally (when λ>300 nm).